Public private partnerships for irrigation: Expanding access or increasing inequality - Bernier, Quinn; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2015)
Public Private Partnerships for irrigation and otherdevelopment is becoming a widely accepted model forfinancing future agricultural and overall economic development and was part of the ‘toolkit’ of the Third International Conference on Financing for Development that took place in Addis Ababa in July 2015 to approve a framework for financially supporting the Sustainable Development Goals and the post-2015 Agenda. However, the Outcome Document of the Conference”1 cautioned that such projects “should share risks and reward fairly, include clear accountability mechanisms and meet social and environmental standards” and outlined a need to “build capacity to enter into public-private partnerships, including with regard to planning, contract negotiation, management, accounting and budgeting for contingent liabilities”. This policy note offers guidance on how to work toward these objectives, presenting emerging findings from a research project implemented by IFPRI together with partners from Ghana and Tanzania, investigating Models of Public Private Partnerships for Irrigation Development. It attempts to identify the institutional arrangements that can best meet the social, development, and environmental objectives of PPPs.